On gamma-ray emission from pulsar magnetosphere - Mofiz, U. A.; Bhattacharya, Dipen (BRAC University, 2010)
Pulsars, a class of rotating neutron stars, are one of the most interesting objects of nature. Although most pulsars have been detected in the radio range, a handful of them are active in gamma rays. In recent years, significant progress has been made in the understanding of the gamma-ray emission processes from pulsars. In this work, we review the different models that are being put forth to explain the pulsar emission, the relation between pulsars and the unidentified gamma-ray sources observed by the Energetic Gamma Ray Experiment Telescope (EGRET) instrument. We present our recent study of plasma modes in the pulsar magnetosphere and discuss briefly the future of gamma-ray astronomy.